The Effect of Discipline on Employee Performance - Yhonanda Harsono; Turmuzi; Indah Pertiwi (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study aims to determine the effect of discipline on employee performance at PT. Pasti Jaya Tehnik Tangerang. The population in this study consisted of employees of PT. Pasti Jaya Tehnik Tangerang. The sample used was 30 employees of PT. Pasti Jaya Tehnik Tangerang. This research is quantitative in nature. The data analysis methods used include validity testing, reliability testing, product-moment correlation, coefficient of determination, simple linear regression, and significance testing (t-test). Based on the results of the study, it is known that discipline (X) and employee performance (Y) show that discipline at PT. Pasti Jaya Tehnik Tangerang has a positive and significant effect on employee performance. The correlation result is 0.695, indicating a strong relationship. The coefficient of determination shows that discipline contributes 48.31% to employee performance at PT. Pasti Jaya Tehnik Tangerang, while the remaining 51.69% is influenced by other factors not examined in this study. The discipline variable as the independent variable and employee performance as the dependent variable show a calculated t-value of 5.114, while the t-table value is 2.048 (tcalculated > ttable), meaning that H0 is rejected and Ha is accepted.